2002
DOI: 10.1021/jf020494e
|View full text |Cite
|
Sign up to set email alerts
|

Extractives Content in Cooperage Oak Wood during Natural Seasoning and Toasting; Influence of Tree Species, Geographic Location, and Single-Tree Effects

Abstract: The chemical composition of cooperage oak wood is highly variable, depending upon the tree species (Quercus robur L. versus Quercus petraea Liebl.), its geographic location, and the single-tree effect. In the process of cask-making, natural seasoning and toasting contribute strongly to the modification of the oak wood chemical composition and therefore influence wine cooperaging. HPLC and GC quantification of ellagitannins and volatile compounds such as whiskey-lactones, eugenol, and vanillin over a sample set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(158 citation statements)
references
References 25 publications
11
143
0
4
Order By: Relevance
“…9 This was observed for Hungarian and Russian oak samples but the opposite was true for American and French oak samples. This could be explained by a possible over-toasting of the latter two samples that could have caused a further decomposition of the compound.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…9 This was observed for Hungarian and Russian oak samples but the opposite was true for American and French oak samples. This could be explained by a possible over-toasting of the latter two samples that could have caused a further decomposition of the compound.…”
Section: Resultsmentioning
confidence: 91%
“…4,5 Oak wood treatments such as seasoning and toasting during cooperage, as well as factors like tree species, geographic location and single tree variations, can modify both the physical and chemical qualities of the wood. [6][7][8][9][10] Odour is a sensation produced after the stimulation of the olfactory receptors in the nasal cavities by suitable chemical structures in the gaseous form, at concentrations greater than their odour detection and recognition thresholds. However, synergistic and antagonistic effects of volatile compounds in mixtures can respectively reduce and increase odorant thresholds, thus influencing their perception.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the concentration of ellagitannins is affected by a large number of interdependent factors, including the species (Canas et al, 2000;Doussot et al, 2002;Jordão et al, 2007), forest origin (Doussot et al, 2002;Jordão et al, 2007), heartwood age (Matricardi and Waterhouse, 1999), grain coarseness (Jordão et al, 2007) among others. Some authors (Masson et al, 1995;Doussot et al, 2002) reported that species discrimination and especially the species-provenance combination are the main factors determining tannin levels. Therefore, more studies about the different origin, anatomical aspect of this new oak source and ellagitannin concentration should be carried out.…”
Section: Ellagitanninsmentioning
confidence: 99%
“…Moreover, the economic importance of this wood species is highlighted by the numerous publications that approached problems related to the wood structure and its quality, the specific defects that appeared, the efficiency in veneer cutting, the genetic variations, the genetic control of various characteristics, and the influence of the manufacturing features on the efficiency in veneer (Raczkowska and Fabisiak 1991;Savill et al 1993;Zhang et al 1994;Mosedale et al 1996;Feuillat and Keller 1997;Kremer and Zanetto 1997;Doussot et al 2002;Le Moguédec et al 2002;Mercker and Hopper 2004;Alberto et al 2011;Kruch 2011;Moldovan 2011;Moroşanu 2012;Dumitrascu et al 2013;Musat et al 2016;Rohumaa et al 2016;Denes et al 2017;Pangh and Doosthoseini 2017).…”
Section: Introductionmentioning
confidence: 99%